Filosofický odkaz Luciena Lévy-Bruhla - Miloš Kratochvíl (AntropoWebzin, 2011)
The main aims of the following paper are to sketch general features of Lévy-Bruhl´s attitude to philosophy and its history and to show influence of his thought to 20th century philosophy of science. Lévy-Bruhl´s effort in ethnology and social anthropology, rooted in his philosophical views on human spirit, is presented as an insrument or a method to establish new and scientific theory of knowledge. His work is not presented only as a chapter belonging to history of philosophy, but also to show its influence on some of the most important persons in philosophy of science, namely Piaget, Bachelard and Koyré.